Evidence of weak ferromagnetism in doped plasticized polyaniline (PANI-DDoESSA)0.5 from electron spin resonance measurements - Santana, V. T. [UNESP]; Nascimento, O. R.; Djurado, D.; Travers, J. P.; Pron, A.; Walmsley, L. [UNESP] (IOP Publishing, 2013)
X-band electron spin resonance (ESR) measurements have been performed on a conducting free-standing film of polyaniline plasticized and protonated with di-n-dodecyl ester of sulfosuccinic acid (DDoESSA). The magnetic field was applied parallel and perpendicular to the plane of the film. At around 75 K a transition is observed from Pauli susceptibility to a localized state in which the spin 1/2 polarons behave as spin 1/2 dimers. A rough estimation of the intradimer and interdimer exchange constants is obtained. Below 5 K, ESR data reveal a weak ferromagnetism with the Dzyaloshinskii-Moriya vector mainly oriented in the plane of the film. The existence of a relatively well-defined n-fold axis along the chain direction in the crystalline regions confers a symmetry compatible with such analysis. © 2013 IOP Publishing Ltd.
Keywords: A transitions; Chain direction; Crystalline regions; Dzyaloshinskii-moriya; Electron spin resonance measurements; Exchange constants; Freestanding films; Localized state; Protonated; Rough estimation; Spin 1/2; Weak ferromagnetism; X-band electron spin resonances; Polyaniline; Ferromagnetism